2021
DOI: 10.1021/acscatal.1c01702
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Clusters on Nitrogen-Doped Carbon are Highly Selective for CO2 Electroreduction to CO

Abstract: The electrochemical reduction of CO2 (eCO2RR) using renewable energy is an effective approach to pursue carbon neutrality. The eCO2RR to CO is indispensable in promoting C–C coupling through bifunctional catalysis and achieving cascade conversion from CO2 to C2+. This work investigates a series of M/N–C (M = Mn, Fe, Co, Ni, Cu, and Zn) catalysts, for which the metal precursor interacted with the nitrogen-doped carbon support (N–C) at room temperature, resulting in the metal being present as (sub)­nanosized met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 90 publications
3
34
2
Order By: Relevance
“…SACs incorporating metals other than Cu can also undergo agglomeration, however, the degree of M 0 formation is typically much lower than that of Cu-SACs and often not reversible 20 , 21 . Therefore, the possible causes behind cluster formation and the reversibility of this process must be understood through assessment of specific Cu-based examples.…”
Section: Understanding Reversible Cluster Formationmentioning
confidence: 99%
“…SACs incorporating metals other than Cu can also undergo agglomeration, however, the degree of M 0 formation is typically much lower than that of Cu-SACs and often not reversible 20 , 21 . Therefore, the possible causes behind cluster formation and the reversibility of this process must be understood through assessment of specific Cu-based examples.…”
Section: Understanding Reversible Cluster Formationmentioning
confidence: 99%
“…As a result, the optimized catalyst displays a superior bifunctional oxygen electrocatalysis performance with a small potential gap of 0.67 V. A series of sub‐nanometer transition metal (Mn, Fe, Co, and Ni) hydroxide clusters loaded on N‐doped carbon support were synthesized and studied in CO 2 RR. [ 87 ] It found that Fe‐, Co‐, and Ni‐based hydroxide clusters display high activity and selectivity toward CO 2 to CO conversion, which is attributed to the phase‐contraction of metal hydroxide clusters with HCO 3 − insertion.…”
Section: Support–cluster Interactionsmentioning
confidence: 99%
“…Recently, Li et al [ 27 ] studied a series of M/NC catalysts characterized by N‐doped carbon hosting highly dispersed metal oxide particles, where the Ni/NC sample showed high activity and selectivity for CO 2 RR. Their findings suggest that a synergy between (sub)‐nano metal oxide clusters and N defects or MN x are key to the high performance of M/NC catalysts.…”
Section: Introductionmentioning
confidence: 99%